2008
DOI: 10.4141/cjss07042
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in the greenhouse gas emissions from the Canadian dairy industry

Abstract: . 2008. Long term trends in the greenhouse gas emissions from the Canadian dairy industry. Can. J. Soil Sci. 88: 629Á639. Estimates of the efficiency of mitigation measures on reducing greenhouse gas (GHG) emissions from the agricultural sector are required. In this paper, recently calculated dairy GHG emissions for 2001 were extrapolated back to 1981 for census years using an index. The index was verified by comparing it with estimates based on the Intergovernmental Panel on Climate Change (IPCC) methodology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Emissions associated with culled dairy cows for 2011 were estimated using relevant coefficients developed for the allocation of GHG emissions to meat and milk in Canada (McGeough et al 2012). According to Dyer et al (2008), between 1981 and 2001, Canadian milk production increased by 48%, while GHG emission intensity decreased by 35%. On the basis of this, the coefficients derived from McGeough et al (2012) were multiplied by a factor of 1.04 for slaughtered dairy cows in 1981.…”
Section: Estimating Ghgsmentioning
confidence: 99%
“…Emissions associated with culled dairy cows for 2011 were estimated using relevant coefficients developed for the allocation of GHG emissions to meat and milk in Canada (McGeough et al 2012). According to Dyer et al (2008), between 1981 and 2001, Canadian milk production increased by 48%, while GHG emission intensity decreased by 35%. On the basis of this, the coefficients derived from McGeough et al (2012) were multiplied by a factor of 1.04 for slaughtered dairy cows in 1981.…”
Section: Estimating Ghgsmentioning
confidence: 99%
“…Subsequently however, the International Dairy Federation [38] suggests that about 15% of these emissions are attributable to the beef sector. Assuming this allocation of emissions from the dairy sector [18,39] increased the mean beef carbon footprint for Canada by about 5% (Table 2c). On a regional basis, inclusion of emissions allocated from the dairy sector can have a very different impact on the carbon footprint.…”
mentioning
confidence: 99%
“…Live weights: Unlike the mid-life live weights used to calculate feed consumption in the original ULICEES calculations [8][9][10][11][12][13], Dyer et al [18] found that the live weights used to calculate protein production had to reflect the weights at the time of slaughter. Feedlot operators feed cattle destined for slaughter to a target weight of around 635 kilograms [25].…”
Section: Protein Production Dynamicsmentioning
confidence: 99%
“…ULICEES calculates the emissions of CH 4 , N 2 O, and fossil CO 2 from livestock production in Canada [6]. ULICEES has defined the GHG emission budgets for beef, dairy, pork, poultry, and sheep [8][9][10][11][12][13]. ULICEES calculations have also been used to assess the competition for land between cattle and biodiesel feedstock production [14,15], and between livestock feed production and food or industrial crop production [16], the benefit of eco-grazing sheep and cattle [17], comparing the carbon footprints of plant and livestock protein [7], and the protein-based carbon footprints of different livestock types [18].…”
Section: Introductionmentioning
confidence: 99%